Pembiasaan Tadarus Al-Qur’an dalam Meningkatkan Kecerdasan Spiritual Siswa di SMP Muhammadiyah 7 Wuluhan Jember - Ines Talita Al Hafiz; Hairul Huda; Badrut Tamami (Jurnal Ilmu Pendidikan, Sosial dan Humaniora, 2026)
The habit of reading the Qur'an is a form of religious activity that is carried out routinely in the school environment to shape the character and spiritual intelligence of students. This activity not only aims to improve the ability to read the Qur'an, but also to instill spiritual values ​​such as sincerity, peace of mind, discipline, and a sense of responsibility. This study uses a qualitative approach with a descriptive method. Data collection techniques are carried out through observation, in-depth interviews, and documentation. The subjects of the study consisted of Islamic religious education teachers, tadarus instructors, and students. The results of the study showed that tadarus activities were carried out every morning before lessons began and had become a positive culture that was welcomed by the entire school community. This habituation process was well structured through teacher supervision and mentoring by students who were more proficient in reading the Qur'an. Based on the research findings, the habituation of tadarus Al-Qur'an had a significant impact on increasing students' spiritual intelligence. This can be seen from changes in students' attitudes who are more patient, humble, and able to control emotions in everyday life. Tadarus activities also strengthen students' spiritual relationship with Allah SWT and foster awareness in carrying out worship. Thus, the habit of reciting the Qur'an can be used as an effective strategy in forming a generation that is not only intellectually intelligent, but also spiritually superior.